Morphology and chemical composition of polymetallic nodules from the Clarion-Clippertone Zone, the Indian Ocean and Rio Grande Rise, a comparative study - Benites, Mariana (2017)
Deep sea polymetallic nodules are concretions of manganese and iron oxides formed around a nucleus. They accrete either hydrogenetically - metals precipitate from the seawater - or diagenetically - metals precipitate from the sediment pore water. The accretion process affects both the nodules morphology and geochemistry. In this study, fourteen polymetallic nodules from four ocean regions, namely the Clarion-Clippertone Zone (Northeast Pacific Ocean), the Central Indian Basin (Central Indian Ocean), the Mascarene Basin (West Indian Ocean), and the Rio Grande Rise (Southwest Atlantic Ocean), were used to compare morphological and geochemical aspects between the different oceanic regions. Computed Tomography (CT) was applied to study the nodules internal structure. Scanning Electron Microscopy (SEM) was used to describe the micro layers within the nodules. Chemical composition of growth layers and nuclei was determined by both Micro X-ray Fluoscence (μ-XRF) and Laser Ablation Inductively Coupled Plasma Mass Spectroscopy (LA-ICP-MS). Finally, X-ray Absorption Near Edge Spectroscopy (XANES) was performed in order to determine the speciation (i.e., the oxidation state) of Mn and Fe. Polymetallic nodules from the Central Indian Basin are diagenetic and the ones from the Mascarene Basin and the Rio Grande Rise are hydrogenetic, while nodules from the Clarion-Clippertone Zone are of mixed type. However, the dominant accretion process varies across the nodules resulting in inhomogeneous layer textures and chemical composition. Strong Mn and Fe fractionation occurs in the diagenetic and mixed type nodules accompanied by fractionation of the trace elements Ni, Cu, Co and Ti. Mn and Fe are present in the nodules mainly as oxidized species Mn4+ and Fe3+, independently of the degree of fractionation. Schematic models of the nodules environment of formation are proposed, in which and the fractionation of Mn and Fe is possibly the result of the variation of the redox front depth through time.